Contribution of E-Business Success to Achieving Competitive Advantage in MSMEs - Sri Rezeki; Pristyono; Sipnarong Kanchanawongpaisan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The success of marketing implementation in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia today cannot be separated from the use of application-based digital technology such as websites, online platforms, and social media. This study aims to examine the influence of social media, influencer marketing, and content marketing on the success of MSMEs, using indicators that are relevant to the research problem. The type of research used is descriptive with a quantitative approach. Data collection techniques are carried out through questionnaires and interviews. The population of this study is MSMEs spread across various regions in Indonesia, with a total of 526,261 units. The sample determination used the Slovin formula and obtained 100 respondents as a sample representing the population. The results of the study show that influencer marketing, content marketing, and social media marketing are independent factors but have a direct influence on the success of MSMEs. In addition, business success has also been shown to have a significant influence on increasing competitive advantage. The results of this study underline the importance of digital marketing strategies in supporting the growth and competitiveness of MSMEs in the era of digital transformation.